2020
DOI: 10.1007/s42844-020-00023-5
|View full text |Cite
|
Sign up to set email alerts
|

“I Wouldn’t Be Here Without Them”: Resilience in Youth Exposed to Intimate Partner Violence

Abstract: The aim of this qualitative study was to investigate and describe the coping strategies that young persons exposed to intimate partner violence (IPV) use to effectively cope with the traumatic experience of growing up in an IPV-affected family. We conducted a qualitative investigation in which we drew on concepts of the constructivist grounded theory method to develop a resilience model that reflects our understanding of the subjective and contextual experiences of the young persons included in our study. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 75 publications
2
10
0
4
Order By: Relevance
“…The importance of this role for initiating and maintaining prosocial behaviour offers an appealing opportunity; current interventions designed to promote the well‐being of children exposed to IPV currently do not take sibling relationships into account, but could be adapted to take better advantage of the potentially significant influence of older siblings (Latzman et al., 2019). Consistent with our results, recent work has found that young people report their supportive sibling relationships as a key component of their resilience in IPV‐affected families (Cameranesi et al., 2021).…”
Section: Discussionsupporting
confidence: 93%
“…The importance of this role for initiating and maintaining prosocial behaviour offers an appealing opportunity; current interventions designed to promote the well‐being of children exposed to IPV currently do not take sibling relationships into account, but could be adapted to take better advantage of the potentially significant influence of older siblings (Latzman et al., 2019). Consistent with our results, recent work has found that young people report their supportive sibling relationships as a key component of their resilience in IPV‐affected families (Cameranesi et al., 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Results indicate that perceived self-efficacy and support from others tend to be related to psychological adjustment [65]. In terms of individual characteristics, analyses of IPV exposure and resilience outcomes have yielded evidence that maternal education level predicted resilience profiles, although gender and ethnicity did not always show significant results [66]. Kassis et al [10] found that only female gender predicted one's assignment to the resilient group versus the non-resilient group in two waves, and migration background (In Switzerland, due to migration policy and the cultural context [67], people with a migration background are either foreign nationals or naturalized citizens according to the Federal Statistical Office [68].…”
Section: Protective and Sociodemographic Factors As Predictorsmentioning
confidence: 99%
“…If we look at the existing empirical research on resilience patterns, we find that similar patterns are found again and again. Cameranesi [55], who specifically examined IPV exposure from a psychopathology perspective, found four adjustment profiles: resilient, multiple severe problems, multiple mild problems, and externalizing problems. Kassis et al [10] also found four resilience and well-being patterns despite physical parental violence experiences, which they based on the dual-factor model of mental health, which include the resilient, troubled, vulnerable, and non-resilient.…”
Section: Resilience Trajectories Of Youth's Ipv Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Although companion animals are often used as tools for abuse, they can also play an important role in one's experience of abuse, offering victims a sense of emotional support Animals, Abuse and COVID-19 Lockdown 6 and comfort and a 'safe-haven' (Flynn, 2000a(Flynn, , 2000b. Animals can have therapeutic potential, being important coping mechanisms during times of adversity, especially for vulnerable populations, increasing resilience, and buffering against the development of psychopathology (Cameranesi et al, 2021;Hawkins et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%